Review Of Release Of Medical Record Information As A Guarantor Of Legal Aspects Of Patient Data Confidentiality - Tiara; Mega Ermasari Muzuh; Niska Salsiani Sinta (International Journal of Multidisciplinary Learners, 2025)
Management of the release of medical record information is often overlooked and does not receive special attention in health care facilities. Inadequate protection of the confidentiality of patient medical information can trigger medical disputes between parties involved in the provision of health services that have an important role in this study. The purpose of this study is to identify the flow of implementation of the release of medical record information that functions as a guarantee in maintaining the legal aspects of patient data confidentiality. This study also aims to identify units related to the implementation of the provision of medical record information as a step to protect the confidentiality of patient data. In addition, this study will identify the types of information released during the disclosure of information that functions as a legal guarantee in maintaining the confidentiality of patient data at the Buton Regency Hospital. This study applies a qualitative descriptive method, with data collection carried out through direct observation and interviews. Where the results of the study show that the flow of the release of medical record information involves verification of patient identity and consent, and follows the principle of "need to know". The procedure for releasing information is regulated by SOP, although there are still discrepancies in its implementation. Units related to this process include hospital management, head of administration, service units, medical staff and nursing staff. The information released includes domestic violence reports, sexual assault reports, and accident reports, with certain conditions such as approval from the treating doctor.